A comparative grammar of British English dialects : agreement, gender, relative clauses - Kortmann, Bernd, 1960- (Topics in English linguistics, 2005)
This volume offers qualitative as well as corpus-based quantitative studies on three domains of grammatical variation in the British Isles. All studies draw heavily on the Freiburg English Dialect Corpus (FRED), a computerized corpus for predominantly British English dialects comprising some 2.5 million words. Besides an account of FRED and the advantages which a functional-typological framework offers for the study of dialect grammar, the volume includes the following three substantial studies. Tanja Herrmann's study is the first systematic cross-regional study of relativization strategies for Scotland, Northern Ireland, and four major dialect areas in England. In her research design Hermann has included a number of issues crucial in typological research on relative clauses, above all the Noun Phrase Accessibility Hierarchy. Lukas Pietsch investigates the so-called Northern Subject Rule, a special agreement phenomenon known from Northern England, Scotland and Northern Ireland. His study is primarily based on the Northern Ireland Transcribed Corpus of Speech, but also on the FRED and SED data (Survey of English Dialects) for the North of England. Susanne Wagner is concerned with the phenomenon of pronominal gender, focussing especially on the typologically rather unique semantic gender system in the dialects of Southwest England. This volume will be of interest to dialectologists, sociolinguists, typologists, historical linguists, grammarians, and anyone interested in the structure of spontaneous spoken English